Artificial Intelligence (AI) Based Public Service Innovations in Improving the Effectiveness of State Administration in the Society 5.0 Era in Medan City - Khairuddin Tampubolon; Muhamad Hendry Surya; Elazhari Elazhari (Universitas Medan Area, 2026)
The development of digital technology in the Society 5.0 era is driving the government to transform public services toward a more effective, efficient, transparent, and adaptive state administration system. One innovation with significant potential is the application of Artificial Intelligence (AI) in public service delivery. This study aims to analyze the implementation of AI-based public service innovations in improving the effectiveness of state administration in Medan City and to identify factors that support and hinder its implementation. The research focuses on the use of AI in administrative services, public complaint management, data processing, and digital technology-based decision-making. This study used a qualitative approach with descriptive methods. Data were collected through in-depth interviews, observations, and documentation studies. The research informants included the Head of the Medan City Communication and Informatics Office, the Head of the Statistics and Public Information Division, SP4N-LAPOR administrators, users of digital public services, and academics in the fields of public administration and digital transformation. Data analysis was conducted using the Miles and Huberman interactive model, encompassing the stages of data reduction, data presentation, and conclusion drawing. Data validity was tested using source and method triangulation techniques. The research results show that the application of AI contributes positively to increasing the effectiveness of public administration by accelerating service processes, improving data processing accuracy, bureaucratic efficiency, and increasing transparency and accountability in public services. The use of chatbots, automated public complaint classification, and AI-based data analysis can improve service quality and public satisfaction. However, AI implementation still faces various obstacles, including limited digital infrastructure, low human resource competency, disparities in technology access, and challenges related to data security and the ethical use of AI. This study concludes that AI-based public service innovation is an effective strategy to support the modernization of public administration in Medan City in the Society 5.0 era. Successful implementation requires comprehensive regulatory support, strengthened digital infrastructure, enhanced staff competency, personal data protection, and synergy among stakeholders to ensure sustainable public service transformation and a focus on improving the quality of public service.